Narrative Review: Ethnomedicinal Study of Skin Diseases - Asmara Yauma Putri Farah Diba; Neneng Rachmalia I. Mukhlishah; Kurniasih Sukenti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Infectious skin diseases in West Nusa Tenggara Province are listed as one of the ten most widespread diseases. Treatment for skin disorders can involve both medical and non-medical approaches. Ethnomedicine offers a way to investigate the applications of medicinal plants and can serve as a first step towards the discovery of new drugs. The purpose of this article is to explore the types of plants used in traditional skin disease treatments. The research results found that plants that can be used for skin disease treatment are predominantly betel, galangal, and members of the Zingiberaceae family. Then, other plants are tobacco, nettle (Toxicodendron radicans), brotowali (Tinospora arisp), kanangas (Ximenia sp.), pomegranate (Punica granatum), grepek (Erythrina sp.), ciplukan (Physalis angulate), water lettuce (Nasturtium microphyllum), lily (Chlorophytum comosum), kesum (Polygonum minus), gelinggang (Cassia alata), cogongrass (Imperata cylindrica), neem (Azadirachta indica), papaya (Carica papaya), mahkota dewa (Phaleria macrocarpa), teki (Cyperus rotundus), lime (Citrus aurantiifolia) and kedondong pagar (Lannea coromandelica), jackfruit (Artocarpus heterophyllus), rice (Oryza sativa), tamarind (Tamarindus indica), coconut milk (Lannea coromandelica), lamtoro (Leucaena leucocephala), sambiloto (Andrographis paniculata), frangipani (Plumeria alba), iodine (Jatropha multifida), and binahong (Anredera cordifolia). The use of medicinal plants by various communities significantly impacts public health and ecosystems. Utilizing these plants can reduce dependence on synthetic drugs and mitigate negative impacts on the environment. Ethnomedicine can further enhance the understanding and appropriate and safe application of medicinal plants, while supporting the preservation of community customs and heritage.